2017
DOI: 10.1146/annurev-med-042915-103905
|View full text |Cite
|
Sign up to set email alerts
|

Highly Effective New Treatments for Psoriasis Target the IL-23/Type 17 T Cell Autoimmune Axis

Abstract: Psoriasis vulgaris, affecting the skin, is one of the most common organ-specific autoimmune diseases in humans. Until recently, psoriasis was treated by agents or approaches discovered largely through serendipity. Many of the available drugs were inherently quite toxic when used as continuous treatment for many years in this chronic disease. However, an increasing understanding of disease-specific immune pathways has spurred development of pathway-targeted therapeutics during the past decade. Psoriasis is now … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
151
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 150 publications
(152 citation statements)
references
References 74 publications
1
151
0
Order By: Relevance
“…trauma or infection) in the pre-psoriatic skin, T17-producing cells in the skin produce substantial amounts of IL-17 (IL-17A/IL-17F), as well as TNF, IL-26, and IL-29 (IFN-λ1). 46 Together, these cytokine signals create a “feed forward” inflammatory response in keratinocytes by activating CCAAT-enhancer-binding protein beta (C/EBPβ) or delta (C/EBPδ), signal transducer and activator of transcription 1 (STAT1), and nuclear factor kappa B (NFκB), which lead to the upregulation of a number of keratinocyte-derived inflammatory products (Figure 2). This “feed forward” response is self-amplifying and, ultimately, drives the development of mature psoriatic plaques by inducing epidermal hyperplasia, regulating epidermal cell proliferation, and recruiting leukocyte subsets into the skin.…”
Section: The Pivotal Role Of Il-17 In Updated Disease Models Of Psorimentioning
confidence: 99%
See 1 more Smart Citation
“…trauma or infection) in the pre-psoriatic skin, T17-producing cells in the skin produce substantial amounts of IL-17 (IL-17A/IL-17F), as well as TNF, IL-26, and IL-29 (IFN-λ1). 46 Together, these cytokine signals create a “feed forward” inflammatory response in keratinocytes by activating CCAAT-enhancer-binding protein beta (C/EBPβ) or delta (C/EBPδ), signal transducer and activator of transcription 1 (STAT1), and nuclear factor kappa B (NFκB), which lead to the upregulation of a number of keratinocyte-derived inflammatory products (Figure 2). This “feed forward” response is self-amplifying and, ultimately, drives the development of mature psoriatic plaques by inducing epidermal hyperplasia, regulating epidermal cell proliferation, and recruiting leukocyte subsets into the skin.…”
Section: The Pivotal Role Of Il-17 In Updated Disease Models Of Psorimentioning
confidence: 99%
“…46 The increased proliferation of epidermal keratinocytes is likely further potentiated by IL-22, and possibly IL-20, as both of these cytokines are also activators of STAT3. 52, 53 This marked thickening of the rapidly proliferating epidermis is accompanied by retention of the keratinocyte nucleus (parakeratosis), as well as upregulation of IL-17-induced transcription factors (e.g.…”
Section: The Pivotal Role Of Il-17 In Updated Disease Models Of Psorimentioning
confidence: 99%
“…DITRA and non-monogenic psoriasis may have pathophysiological features in common,5 meaning that complex interactions between innate and adaptive immune systems may be involved 6–10. Failure to thrive in DITRA children may be explained by exudative cutaneous protein loss, systemic inflammatory activity, gastrointestinal inflammatory involvement and/or the late repercussions of a lack of early maternal attachment.…”
mentioning
confidence: 99%
“…IL-23 plays a pivotal role in the pathogenesis of psoriasis (40) and one study (41) describes patients with psoriasis who showed a reduction in nevus numbers in the psoriatic lesions. Another study (42) observed that compared with control subjects, psoriatic patients had fewer nevi overall, fewer nevi less than 5 mm, and fewer congenital nevi.…”
Section: Discussionmentioning
confidence: 99%